(untitled) - McCarty, Bill (New York, 2001)
Essential skills for first-time programmers! PHP 4: A Beginner's Guide explains the fundamentals of this hot programming language. You'll learn to create forms, work with functions, use cookies, access relational databases, and debug PHP scripts. The modular approach of this series--including drills, sample projects, and mastery checks--makes it easy to learn PHP 4 programming quickly.
Keywords: PHP (Computer program language),PHP (Ngôn ngữ lập trình máy tính)